Dietary risk factors for testicular cancer - Garner, Michael J (University of Ottawa (Canada), 2003)
Although testicular cancer is a relatively rare cancer in Canada, accounting for only 1.1% of all malignant neoplasms in males, it is the most common cancer among men 20 to 45. Understanding of the causes of testicular cancer risk in general, and the association with diet in particular, remains limited. Data from the National Enhanced Cancer Surveillance System were used to explore the relationship of diet and testicular cancer risk. There were 601 cases of testicular cancer and 744 controls available for study. We systematically examined 17 food groups, 15 nutrients, and 7 individual foods based on data collected through a 69-item food-frequency questionnaire. Our results suggest that higher dairy product intake, specifically cheese, is associated with a higher risk of testicular cancer in Canadian males. Risk differences were observed between histological subtypes of testicular cancer. This thesis provides a basis for future studies designed to address testicular cancer etiology.
Keywords: Health Sciences, Nutrition.; Health Sciences, Oncology.